Effects of a Participatory School-Based Intervention on Students' Health-Related Knowledge and Understanding - Strobl, Helmut; Ptack, Katharina; Töpfer, Clemens; Sygusch, Ralf; Tittlbach, Susanne (Frontiers in Public Health, 2020)
Introduction The development of knowledge and understanding in relation to movement and health is a basic requirement to facilitate lifelong engagement in physical activity with its accompanying possible health benefits. To train teachers in applying adequate strategies, implementation studies have often shown little acceptance of traditional top-down approaches. Thus, the purpose of the Health.edu project was to develop, implement and evaluate effective and feasible measures addressing students’ health-related knowledge and understanding (HKU) in physical education (PE) via a participatory approach. Materials and Methods For evaluation, a controlled pre-post-test study with 233 students from eight different secondary schools in Germany was carried out. Four schools (with two PE teachers at each school) comprised the intervention group and they participated in a one-year participatory planning process to conceptualise and implement evidence-based PE lessons addressing students’ HKU. Control schools carried out their regular PE lessons. Evaluation followed a mixed-methods research design, assessing program implementation via written documentary technique as well as program effectiveness using a standardized questionnaire. Results Results show a significant intervention effect on students’ HKU with a medium effect size. However, due to the participatory process, there were considerable differences between the intervention schools that were involved. Student’s HKU improved most in schools where program implementation corresponded to relevant principles of fostering HKU. Discussion The present study purposefully dispensed with any structured intervention programmes for PE teachers to follow. The results show the potential effects of this participatory approach to strengthen student’s HKU. However, the participatory planning does not always work in the intended manner, emphasizing that numerous contextual factors influence the implementation process.